Afrikanske smede - Nicolaisen, Johannes (Kuml, 1962)
African Smiths Cultural-historical and sociological problems illuminated by studies among the Tuareg and by comparative analysis In KUML 1957 in connection with a description of slavery among the Tuareg, I also gave a short survey of this great Berber pastoral group in the Sahara and the Sudan, and its geographical distribution was shown on a map, page 93. In this article I shall describe another negroid group among the Tuareg, the smiths, letting the material presented serve as a basis for consideration of a number of problems connected with the cultural-historical and sociological position of smiths in Africa and adjacent regions. The Tuareg name for a smith is éned (pl. ineden). The smiths are, in contrast to the Tuareg, predominantly negroid, but not as pronouncedly so as the slaves. Indeed, one can also encounter smiths who are comparatively light of skin and with features that seem to indicate europid influence. There are also Tuareg who believe that the Tuareg smiths were originally europid lightskinned people, coming from the north and, like so many Tuareg, mixing with people of negroid race in the Sudan. These views on the northern origin of the smiths agree with certain traditions about their original connection with Jewish smiths in Southern Morocco. Furthermore, both the Tuareg smiths and the negroid smiths in Morocco lay claim to Sidna Dawud, i. e. "Our Father David", as patron saint or progenitor, which again seems to indicate connection with Jews. A connection between smiths and Jews in the Sahara is, moreover, far from unlikely. The Jews immigrated to North Africa very early - perhaps already in Phoenician times - and not only in North Africa, but all over the Near East, there is a strong connection between metalworking and Jews. Culturally, there is no essential difference between the smiths and the nomadic Tuareg, apart from their special skill. They dress like Tuareg, undergo Tuareg initiation ceremonies, and their behaviour pattern is determined by the Tuareg kinship system. The everyday language of the smiths is Tuareg, but they have in addition their own language which Foucauld describes as a Berber dialect. The vocabulary of this special smiths’ language, which is called ténet, is, however, very different from that of Tuareg, whereas the noun endings fit a Berber grammar similar to Tuareg. The smiths’ language is, in fact, a secret language only employed when the smiths do not wish the Tuareg to understand what they are saying. Mr. K.-G. Prasse - the expert on Berber languages in the University of Copenhagen - is of the opinion that the secret language of Tuareg smiths is a kind of slang consisting of circumlocutions of everyday words, but derived from nothing but the local dialect itself. The smiths enjoy a certain esteem on account of their craftsmanship, and it is evident that Tuareg material culture would be much impoverished without the many things produced by the smiths; not only weapons and trinkets of metal, but many domestic articles of wood, richly decorated camel saddles and tent poles, etc., which are found in the nomad camps, are the work of the smiths. In addition, stone-working and especially manufacture of the celebrated stone bracelets, worn on the upper arm by most adult Tuareg, are their concern. The wives of the smiths are also highly skilled craftswomen, and the finer leatherwork which adorns sword sheaths, amulet-holders, etc., is superior in quality to anything the nomadic Tuareg woman can produce. What is more, the smiths -both men and women- enjoy a special reputation as musicians and singers and in this capacity perform at many Tuareg festivals, especially weddings. At the camps of chieftains of the southern Tuareg several tents are often found inhabited by smiths who serve the Tuareg chiefs with more than technical skill. By their mere presence the chief gains prestige, and they have moreover the task of collecting taxes from the Tuareg commoners, who are usually described in the literature as vassals. Finally, the smiths have a certain influence as masters of metals. Among the Tuareg, as well as elsewhere in Northern Africa, metals are attributed a certain amount of magical power: silver brings luck, copper and brass are a remedy for various illnesses (e. g. rheumatic illnesses) which are supposed to be caused by the spirits called Kel Asuf (Arabic, jenun), while iron has the power of keeping evil spirits away. This endows the smiths with special powers, exploited by the Tuareg in the struggle with evil. From the above description, one could easily be led to believe that the smiths are highly respected among the Tuareg, but this is not, in fact, the case. Smiths are at one and the same time despised and feared by the Tuareg. They are despised as so many others of negroid race and as others who live by their hands. But the contempt the Tuaregs feel for smiths is closely linked with fear. Why are smiths feared? It is said that they sometimes act as private detectives (e. g., in cases of suspected matrimonial infidelity) and that a smith does not care how he behaves. A smith does what he likes and never hesitates to spread malicious gossip if it suits him. They are feared on these grounds, but even more so because wherever they go they demand gifts of the Tuareg. Actually, a Tuareg is never obliged to give a smith what he asks for, but the Tuareg believe that smiths possess mysterious evil powers, with which they can punish those who do not respond. This evil power, which the Tuaregs of Air call etama or tezma, seems to be of a purely magical nature; it works automatically without the performance of any physical act. In spite of this a Tuareg holds smiths responsible for possessing this power, and a few years ago a Tuareg killed a smith whom he blamed for a camel’s death. The etama-power can kill domestic animals, but not normally people, although it can afflict children with a serious illness, which usually manifests itself in a swollen stomach. This power is thus less feared than the true black magic, which among the Tuareg is first and foremost practised by members of the marabut class. The Tuareg belief in etama-power is exploited by the smiths to extort gifts wherever they go. But at the same time smiths have a special system of payment for their work, a payment which is usually made in kind. For an axe the payment is a half-grown kid or 7 measures of wheat, corresponding to about 17 kg. In addition the smiths of the northern Tuareg have a fixed yearly payment for the repair of mattocks and other agricultural implements, which are used by the settled negro farmers in the oases. There the smiths receive for their work the yield of wheat from one irrigated plot in every cultivated garden -equal to about 10 kg. corn. The Tuareg smiths’ most important work is connected with the processing of iron, which is generally of European provenance. Among the Northern Tuareg there is no extraction of natural iron-ore whatsoever, and one has to go as far south as the Sudanese Tuareg area before iron smelting is encountered. Among smiths south of Air in Damergu it is carried out just as in Northern Nigeria, by smelting in a large earthenware pot, where the ore is laid on charcoal, which is kept alight with the aid of bellows. Smiths in the Iullemmeden Tuareg area around Tahoua and farther south use a tall mud-built furnace, where firing takes place without bellows and occupies a whole day and night. But even in the last-named areas a great deal of European iron is used, being better than the locally extracted product, and iron smelting is moreover difficult work. The tools used in smithery are more or less the same throughout the extensive area inhabited and dominated by the nomadic Tuareg. The most important is surely the bellows, which occur everywhere as double bellows, consisting of two bags made of tanned goatskin, each with an opening at the back with inserted wooden slats and leather straps for the fingers. The front of the two bags is attached to a bifurcated perforated piece of wood, in which two iron pipes are inserted. The bellows are used in such a way that the back of the bag is kept open for the air while filling, and closed by squeezing the two slats together when blowing. The two bags are inflated alternately in this way and an experienced smith can thus direct on the forge a strong and continuous blast of air (see figs. 4 & 11). When the bellows are in use, a special tuyere is placed round the two iron pipes. This is made from unfired clay, which is quickly converted to ceramic material ( figs. 4 & 6). Besides the double bellows, some Tuareg smiths are known to possess single bag-bellows, which I have seen in use by smiths in the region south of Air (fig. 5). In addition to these there is a whole series of tools used by smiths in many places both inside and outside Northern Africa. First and foremost are the jointed tongs, the hammer hafted by a hole in the centre, the head of which is apparently often made of two parts welded together, drifts and chisels of different sizes and the drill used for boring fine metal plates (fig. 9). For melting silver, small crucibles of unfired clay, which of course quickly become converted into refractory material, are used. Finally, there is the anvil, which among the northern smiths is often a block of European iron, whilst the traditional anvil of the Tuareg smiths consists of a massive clubshaped iron spike driven into a stout wooden block (fig. 7). It is recognised that iron was extracted and worked in Middle Eastern cultures as early as 1500-1600 B. C., and that the Danish Iron Age began around 400 B. C. Elsewhere, iron was introduced even later, and it was not used in pre-Columbian America in whose advanced cultures copper, bronze, gold and platinum were none the less worked. It is peculiar that ironworking should arrive so late, especially as iron ores are so widely distributed. The explanation seems to be, however, that iron ore is more difficult to smelt than other metallic ores. It is a condition that the iron takes up carbon during roasting, thus lowering its melting point, and by primitive roasting methods so little carbon is absorbed that it is necessary to increase the supply of air with the aid of some kind of bellows. Therefore, it is only natural that bellows and iron extraction have approximately the same distribution. We know that bellows were found in Ancient Egypt around 1500-1600 B. C. (fig. 17), or somewhat before iron appeared in that region. These Egyptian bellows will be mentioned below in a short summary of the most important types of bellows, which can be divided into five main categories: (1) Bag bellows (figs. 4, 5, 11, 12, 13). These are the bellows described for the Tuareg. The double bag-bellows have an extremely wide distribution, occuring nearly everywhere in North Africa and the Sahara, among many Sudanese peoples, and in East and South Africa. Outside Africa they occur in the Middle East, right over to India and Tibet, and north from there to the central Asiatic steppe areas and the Siberian reindeer nomads. The bag bellows are also stated to occur in a few places in Indonesia, but here they are presumably a recent introduction - perhaps from India. There are some stations in southern Europe and it is probable that bag bellows have had a much wider distribution in European countries. There can be no doubt that the double bag-bellows are derived from the single bag-bellows. This is not only apparent from the two nozzles with which most double bag-bellows are provided. At some places in Africa two single bag-bellows are in fact used to produce the continuous stream of air, by placing them side by side or on either side of the forge. The single type is more restricted in its distribution than the double. It is reported from the Tuareg, the Chawiya Berbers in Aurés, from Kurds and Lurs, and from India. (2) Drum bellows (figs. 14-19, 30) are found as single belolws but much more often double. They are especially characteristic of the western and central parts of Africa in and around the tropical rain-forests, and outside Africa they apparently occur only in parts of India, including Assam and Ceylon, and in Further India. The drum bellows consist of drum-shaped cylindrical containers of earthenware or wood, covered with leather, and in Africa, sometimes plant material. By moving the skin up and down a blast of air is forced through one or two nozzles, and according to the manner in which the bellows are worked, three main types of drum bellows are distinguished: (a) The leather bag is moved up and down with the aid of a small loop fixed to its middle, or by gripping the bag itself. This primitive method is not common and is found only among a few African tribes. (b) The bag is compressed by two sticks of varying length fastened to the middle. This is far the commonest method in Africa. (c) The bellows are worked with the feet. This is not a common method in Africa, being recorded only from a couple of East African tribes. Is was known in Ancient Egypt (fig. 17) and the Asiatic drum bellows are apparently all foot bellows. African drum bellows which are operated with the help of sticks are in certain parts of Central Africa multi-chambered. Drum bellows are normally closed and without any valve mechanism for air supply. (3) Cylindrical ring bellows (fig. 19). These bellows comprise several different types having in common that air compression is brought about by cylindrical bags dilated with wooden rings. Bellows of this kind with two horizontal cylindrical bags, each provided with a handle, were known in Portugal in the 16th century. A related type seems to occur on the other side of the Mediterranean among the Berber Kabyles east of Algiers. Possibly bellows based on the same principle occur in Morocco. A special kind of cylindrical ring-bellows is the so-called "concertina bellows" (fig. 20) which are met with in certain parts of the western Sudan. These are a kind of drum bellows provided with cylindrical bags dilated by rings of wood. Finally in East Africa, around Dar-es-Salam, special cylindrical bellows provided at the top with a round wooden plate and worked with a stick which is not fastened to the plate but to a leather strap, are met with. This strap covers a little hole in the plate during compression, but leaves it open for air during expansion. (4) Pointed European bellows (figs. 19 & 21). These are the ordinary European bellows, which throughout the Middle Ages and up to the present, have been used in smithery and firing processes in general. As smiths’ bellows they can be double or single, in the latter case with a drawbar, so that the smith standing by the furnace can operate the bellows himself. This type is met with in the Atlas country, where I have seen the Berber Chawiya and Kabyles using it. In Tunis are found double bellows consisting of two small pointed bellows. Possibly the pointed bellows originated in Rome and came to North Africa with the Roman occupation. Elsewhere in the Orient the pointed bellows do not seem to be common, and in many places were presumably introduced by Europeans in recent times. This seems to be true of the African Gold Coast also, where the pointed type is found. With Russian colonists it has penetrated Siberia right over to the Chukchi. (5) Piston bellows (figs. 22 & 23). The air is compressed by pistons in cylinders. Both single and double piston-bellows are found, and can be divided into two main types: (a) Horizontal piston-bellows, which are cylindrical in China and box-like in Korea and Japan. (b) Vertical piston-bellows, which are always cylindrical. They are found all over Indonesia, in Further India and parts of Peninsular India, and in Madagascar. Outside the areas specified piston bellows do not seem to occur, but it is alleged that a kind of square piston-bellows was used in Europe. It will be seen from the above summary that the distribution of the various types of bellows is fairly well known, and general theories on the origin of bellows were offered at an early stage. There is scarcely any doubt that the origin of the bellows should be sought in the simple blowpipe, which is known from both the Old and the New World, but which bellows are the oldest? F. Foy produced a theory in 1909 that the bag bellows had a greater antiquity than the drum bellows, and this theory has won acceptance by many scholars, but in the same year Felix von Luschan published an article on iron technology in Africa, in which he expressed the view that the origin of iron working should be sought in Central Africa and was closely linked to the drum bellows. It seems that the bag bellows have been thought to be specially primitive, because they are usually simple in the sense that the bag is made from little-treated animal skins. If one ignores this evolutionist view, several arguments can be presented to suggest that the drum bellows are older than the open bag bellows. I argue as follows: (1) The drum bellows as foot bellows are known from Egypt as early as 1500-1600 B. C. (fig. 17). (2) In Egypt, as elsewhere in Africa, there is evidence that the drum bellows have been replaced by the open bag-bellows. (3) In Africa, the drum bellows occur especially in the central parts in and around the rain forest area, whereas the bag fellows are found in an almost continuous belt around this region. (4) Drum bellows have a broken distribution, being found both in India and adjacent areas and in Africa. It has to be admitted, however, that the Asiatic and African drum bellows are for the most part separated by busy seas over which many culture elements have been carried to Africa, but both in Africa and Asia drum bellows are found at the edge of the bag-bellows distribution area and far from the parts where iron was presumably first forged. (5) The drum bellows are less effective than the bag bellows, which can compress large masses of air. Hence the frequent use of multi-chambered drum bellows, whilst the bag bellows are only found double. (6) The bag bellows are difficult to use in contrast to the drum bellows. It requires training in a special technique to operate the bag bellows effectively. (7) The drum bellows are normally closed in contrast to the bag bellows, which are, as it were, always open. This seems to point to a greater antiquity for drum bellows compared with open bag-bellows and an investigation into the characteristics connected with African smithery seems to point in the same direction, since there is apparently a tendency to encounter the most primitive tools in just those regions of Africa where the drum bellows dominate or are used to the exclusion of other types. Thus the jointed tongs are apparently seldom found with the drum bellows but almost everywhere where the bag bellows dominate. In the drum-bellows area, branches or a temporary hafting are often used to secure the iron during forging. In the same way the hammer hafted by a hole in the centre is especially tied to the African distribution of the bag bellows, whereas the club-shaped hammer, which is often used in a vertical movement, is more common where the drum bellows predominate. The club-shaped hammer seems rare outside Africa, but occurs as far west as Formosa, which would argue for a great age. Thirdly, the most primitive method of iron smelting, in a pit, is commonest in the central regions of Africa, where the drum bellows dominate. Iron extraction in simple pits demands the use of bellows, and as far as the available comparative material indicates, drum bellows always seem to be used in pit smelting. Thus everything speaks for the antiquity of the drum bellows, but the theory presented here, which is based on ethnographical method, needs the confirmation of archaeology. It is interesting to note that certain sociological features linked with African smithery have approximately the same distribution as the two chief types of bellows. For just as the bag bellows have their chief distribution among nomadic peoples, or in regions which are strongly influenced by nomadic cultures, so we find in this region a marked contempt for smiths, who are also feared in most places. This condition is described in detail above for the Tuareg. More generally, it can be stated that contempt for and fear of smiths are attitudes which are manifest in most of North Africa and in many places in eastern Africa and sporadically towards the south among cattle-rearing peoples. It is probable that it is the same attitude we find in Arabia, where smiths constitute a special endogamous cast, and both fear of and contempt for smiths are widespread attitudes among nomadic and settled Tibetans. Farther north in Central Asia and among Siberian peoples, it is not exactly this attitude which is met with, although there is evidence that the Yakuts regard smiths with superstitious fear even though they also respect them. Smiths are not despised and moreover enjoy a certain religious prestige, which stems, however, from their relation to the evil spirits of the underworld, and not to the good, heavenly spirits. That smiths are despised by pastoral peoples is probably due to the fact that they constitue a foreign, as a rule negroid, element in the population, and likewise because they live by their hands. But this is not the real reason for the Tuaregs’ contempt, which stems first and foremost from the fact that the smiths, who are outside Society, exploit their magical powers to their own advantage and to the possible detriment of the nomadic Tuareg. Smiths are despised by Tuareg in a quite different way from other negroid classes or casts. The relationship between other pastoral peoples and smiths seems to be similar. In Central Africa, in just the region where the drum bellows are typical, a diametrically opposed attitude is encountered. Smiths belong to Society -and enjoy the greatest prestige and respect, in which it can be difficult to distinguish from the literature between "fear" and "respect". The prestige of smiths in Central Africa is so great that there are often family ties between chiefs and smiths. Indeed, there are traditions that the first chief of one people was a smith, and in some places smithery has been so highly esteemed that even the sons of kings were trained in it. It is interesting that roughly the same attitude to smiths and smithery is found in Indonesia. In both Africa and Indonesia, smiths enjoy a great religious prestige, in fact they can become leading figures in religious life. Apparently an investigation into the social position of smiths in Africa gives realistic indication of the social functions of religion. Where smiths are despised, they are kept outside Society and outside religion; where respected, they are placed at the head of Society and religious life. Where smiths are despised the mystical powers seem to be primarily of a magical and not a religious nature. Johannes Nicolaisen.